A Comparison of Prehospital Nonphysician and Hospital Physician Placed Tube Thoracostomy. Issue 7 (July 2020) - Harrell, Kevin N.; Brooks, Dylan E.; Palm, Preston H.; Cowart, Jonathan T.; Maxwell, Robert; Barker, Donald
Background: Prehospital chest decompression can be a lifesaving procedure in severe chest trauma. Studies investigating prehospital chest decompression are mostly European where physicians are assigned to prehospital care units. This report is one of the first to compare demographics and outcomes in patients undergoing prehospital chest decompression by trained aeromedical nonphysician personnel to hospital chest decompression by physicians. Methods: Prehospital tube thoracostomy (PTT) patients were identified from January 2014 to January 2019 and were matched in a 1:2 ratio based on age, Injury Severity Score (ISS), and chest Abbreviated Injury Score (AIS) to patients who underwent hospital tube thoracostomy (HTT) within 24 hours of admission. Results: Forty-nine PTT patients were matched to 98 HTT patients. PTT patients had lower admission Glasgow Coma Scale (GCS), a higher rate of pre-chest tube needle decompression, and higher level 1 trauma activation. PTT were placed sooner (21.9 vs 157.0 minutes, P < .001). Rates of tube malposition, organ injury, tube dislodgement, empyema, and hospital-acquired pneumonia over the course of hospital admission were not significantly different between the 2 groups. PTT patients had longer intensive care unit length of stay (LOS), but similar hospital LOS, and overall mortality. Discussion: This report demonstrates that PTT is performed sooner than hospital placed tubes. Complication rates associated with tube thoracostomy and patient outcomes were not statistically different between PTT and HTT groups.